Serum Ratio of Leptin to Adiponectin in Patients with Chronic Periodontitis and Type 2 Diabetes Mellitus. (12th January 2014) - Jing Ling, Xu; Xin, Meng Huan; Lu, He; Xian'E, Wang; Lin, Zhang
Abstract : Background . Serum ratio of leptin to adiponectin has been reported to be a useful index of insulin resistance. Since these two adipokines could also be involved in many immunoinflammatory reactions, this ratio might be associated with some inflammatory diseases such as periodontitis. The present study aims to explore the difference in serum ratio of leptin/adiponectin among patients with diabetes and periodontitis, patients with periodontitis only, and healthy people and find out the correlation between this ratio and periodontal parameters. Method . 15 patients with chronic periodontitis and type 2 diabetes, 15 patients with chronic periodontitis only, and 15 healthy controls were selected. Clinical indexes and periodontal parameters were recorded and serum leptin and adiponectin levels were tested by ELISA kits. Result. The ratio of leptin/adiponectin is significantly different among three groups; the T2 DM + CP group has the highest ratio (1.91 ± 0.48 ) and the healthy group has the lowest ratio (0.65 ± 0.13 ). What is more, the ratio of leptin/adiponectin has strong positive correlation with periodontal parameters (P < 0.001 ). Conclusions . Chronic periodontitis could influence the level of adipokines in serum and change the ratio of leptin/adiponectin, and the effect would be enhanced combining with type 2 diabetes.